2019
DOI: 10.1016/j.ygyno.2019.02.016
|View full text |Cite
|
Sign up to set email alerts
|

HPV infections and cytologic abnormalities in vaccinated women 21–34 years of age: Results from the baseline phase of the Onclarity trial

Abstract: The impact of HPV vaccination was determined in a cervical cancer screening population from the USA-based, Onclarity Trial. • HPV and cytology testing were determined in 14,153 women, 21-34 years; and compared by vaccination status. • The prevalence of overall HPV, and genotypes 16, 18, 31, and 33/58 were significantly lower in vaccinated women. • Prevalence of ≥LSIL cytology (for any HPV result), and ≥CIN2 (only for HPV 16+ or 18+ cases), was lower in vaccinated women. • Data in this article suggest that "cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Additional limitations include the relatively low vaccination rate (11.3% in ASC-US and 15.5% in LSIL) and the fact this analysis does not take into account the number of prior screens that the subjects had had. Although a larger number of vaccinated subjects would reduce the prevalence of vaccine targeted genotypes and of HPV 16/18 associated ≥CIN2, it would not be expected to change the actual risk hierarchy [28]. Similarly, although subjects with a history of multiple prior negative screens would be expected to have a lower prevalence of ≥CIN2, such a history would not be expected to change the risk hierarchy [29].…”
Section: Discussionmentioning
confidence: 99%
“…Additional limitations include the relatively low vaccination rate (11.3% in ASC-US and 15.5% in LSIL) and the fact this analysis does not take into account the number of prior screens that the subjects had had. Although a larger number of vaccinated subjects would reduce the prevalence of vaccine targeted genotypes and of HPV 16/18 associated ≥CIN2, it would not be expected to change the actual risk hierarchy [28]. Similarly, although subjects with a history of multiple prior negative screens would be expected to have a lower prevalence of ≥CIN2, such a history would not be expected to change the risk hierarchy [29].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in those who continue to be screened with cytology only, as the prevalence of high‐grade cervical abnormalities and the incidence of cervical cancer decline, the proportion of false‐positive findings is expected to increase significantly. There is emerging evidence on screening outcomes from other countries with higher vaccine uptake, 34‐36 and some preliminary data from the United States 37‐39 that show significant declines in cervical abnormalities in vaccinated populations, and which point to the likelihood that future recommendations for cervical cancer screening will need to incorporate HPV vaccination status.…”
Section: Introductionmentioning
confidence: 99%
“…HPV genotyping has been mostly focused on HPV16 and HPV18 due to their high prevalence in cervical cancer, although, other hr-types indicate high positive predictive value (PPV) [8,10]. Earlier studies suggested that extended HPV genotyping provides a better risk stratification and identification of women at increased risk of cervical cancer by simply providing individual risk assessment of HPV positive women [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…HPV oncogenic potential is highly type-dependent as some types are more oncogenic. Many studies have shown that extended genotyping information holds important clinical value for patient management and triage of HPV positive women [8][9][10].…”
Section: Introductionmentioning
confidence: 99%